Development of graphene quantum dots-based optical sensor for toxic metal ion detection - Anas, Nur Ain Asyiqin; Yap, Wing Fen; Sheh Omar, Nur Alia; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Md Ramdzan, Nur Syahira; Saleviter, Silvan (MDPI, 2019)
About 71% of the Earth’s surface is covered with water. Human beings, animals, and plants need water in order to survive. Therefore, it is one of the most important substances that exist on Earth. However, most of the water resources nowadays are insufficiently clean, since they are contaminated with toxic metal ions due to the improper disposal of pollutants into water through industrial and agricultural activities. These toxic metal ions need to be detected as fast as possible so that the situation will not become more critical and cause more harm in the future. Since then, numerous sensing methods have been proposed, including chemical and optical sensors that aim to detect these toxic metal ions. All of the researchers compete with each other to build sensors with the lowest limit of detection and high sensitivity and selectivity. Graphene quantum dots (GQDs) have emerged as a highly potential sensing material to incorporate with the developed sensors due to the advantages of GQDs. Several recent studies showed that GQDs, functionalized GQDs, and their composites were able to enhance the optical detection of metal ions. The aim of this paper is to review the existing, latest, and updated studies on optical sensing applications of GQDs-based materials toward toxic metal ions and future developments of an excellent GQDs-based SPR sensor as an alternative toxic metal ion sensor.